Arbitration in public project disputes in the Law of Saudi Arabia - Alshaikh, Hashem Baker (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify arbitration in public project disputes in the Saudi system, to identify similarities and differences between arbitration and similar systems, to identify types of arbitration in public project disputes in law, to identify the nature of public project disputes in the Saudi system, and to identify the nature of arbitration in project disputes The general and identification of the competent authority to consider public project disputes in the Saudi system, and the original approach was used, which depends on theorizing the particles and their response to a general principle that governs them, and the study reached the most important results, which are: 1.Arbitration is one of the permissible and legitimate matters in Islamic jurisprudence, and the most correct of the sayings of Islamic jurisprudence scholars is that it is permissible and legitimate in general, whether there is a judge in the country or not. 2.Arbitration is similar to the means of settling other disputes, such as judiciary, conciliation, and conciliation, in that it aims at one goal, which is to resolve the dispute between the litigants, and achieve justice, and that the differences between it and arbitration are differences that do not affect the end of disputes. 3.The types of arbitration in public project disputes are three. The first type is optional and compulsory arbitration, and this type is related to the extent of the will of the administrative authority and the contracting party with it to resort to arbitration. The second type is private or free arbitration and institutional arbitration, and this depends on the type of arbitrators. The law and procedures applicable to the dispute. 4.The administrative dispute in the law and that it is a legal means guaranteed by the law for people to protect their rights from confronting the administration through the administrative judiciary, and that there are standards that jurists differ in defining the administrative dispute, and that the most correct among them is the mixed criterion that combines the criterion of public authority and the criterion of public utility.
Keywords: arbitration; public project disputes; the Saudi system